Pengaruh Disiplin Kerja terhadap Kinerja Perangkat Nagari di Nagari Rangkiang Luluih Kecamatan Tigo Lurah Kabupaten Solok - Nurhayati Nurhayati; Rasidah Nasrah; Padrizal Padrizal (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study was carried out on the Apparatus of Rangkiang Luluih Village in Tigo Subdistrict, Solok Regency. The aim of this research was to assess the extent to which Work Discipline impacts the Performance of the Village Apparatus within Rangkiang Luluih Village, Tigo Subdistrict, Solok Regency. The population for this study consisted of 30 employees from the Rangkiang Luluih Village Apparatus. The Total Sampling method was employed for the sampling technique. Data was collected through a questionnaire. According to multiple regression analysis, the Work Discipline variable (X1) influences Performance (Y). The resulting multiple linear regression formula is Y = -1.699 + 0.702 X1 + e. The coefficient of determination indicates that the independent variable (X1) accounts for 95.8% of the variance in the dependent variable (Y), with the remaining 4.2% being affected by other factors not explored in this study. The t-test results for the Work Discipline variable (X1) indicate a significant effect on Performance (Y) since t count exceeds t table. Additionally, the f-test shows that Work Discipline (X1) significantly affects the dependent variable, Performance (Y), as the computed f-value is higher than the critical f-value (311.039 > 3.35), and the significance level is below 0.000, which is less than 0.05.